1990
DOI: 10.1007/bf01977632
|View full text |Cite
|
Sign up to set email alerts
|

Activation of troponin C by Cd2+ and Pb2+

Abstract: Certain heavy metal actions such as Cd2+ and Pb2+ mimic Ca2+ effectively in stimulating calmodulin (CaM). We now show that these cations also activate skeletal muscle troponin C (TnC), a Ca2(+)-binding protein highly homologous to CaM. Like Ca2+, these cations allow TnC to alter its electrophoretic mobility on polyacrylamide gels, and to bind to phenyl-Sepharose. Moreover, they activate TnC to stimulate myofibrillar ATPase. When TnC was removed from the skeletal myofibrils by treatment with trans-1,2-cyclohexa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
2

Year Published

1995
1995
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 45 publications
1
25
0
2
Order By: Relevance
“…Radical scavenging has been related with reduction of in vitro DNA damage and lipid peroxidation and, thus, in an overall decrement in the toxic potential of the fibers. [2,16,17,36,37] Biochemical response of fungi to asbestos fibers: Modification in protein expression: The modification in protein expression following interaction with asbestos may be a fungal response either to physical contact with the fibers or to a possible oxidative stress caused by the fiber or by mobilized iron. The SEM analysis of mycelia grown in direct contact with the fibers showed the physical integrity of hyphae; [25] thus, the extracellular protein pool changes in the presence of fibers are likely to be due to active synthesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Radical scavenging has been related with reduction of in vitro DNA damage and lipid peroxidation and, thus, in an overall decrement in the toxic potential of the fibers. [2,16,17,36,37] Biochemical response of fungi to asbestos fibers: Modification in protein expression: The modification in protein expression following interaction with asbestos may be a fungal response either to physical contact with the fibers or to a possible oxidative stress caused by the fiber or by mobilized iron. The SEM analysis of mycelia grown in direct contact with the fibers showed the physical integrity of hyphae; [25] thus, the extracellular protein pool changes in the presence of fibers are likely to be due to active synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…[13,14] Incubation of the fibers with an aqueous solution of some chelators was reported to inhibit surface reactivity [15] and to decrease DNA damage and lipid peroxidation in vitro. [16][17][18] Synthetic chrysotile with no iron in the structure was recently reported not to be cytotoxic toward human epithelial cells in a culture. [19] Iron extraction from asbestos fibers may also destabilize the lattice if the extraction proceeds for several layers below the fiber surface.…”
Section: Introductionmentioning
confidence: 99%
“…Pb is an effective competitor with Ca for protein binding when equimolar concentrations are used in the test tube. 49,50 If there had been a 1000-fold difference in the molar concentrations of these metals presented to the gut, then additional Ca would not be expected to have a demonstrable additional effect on reducing absorption. This leaves open the possibility that Ca supplementation may still play a role in the treatment of Pb-poisoned children who are dietarily Ca deficient.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Chao et al reported that Pb 2+ produces a biphasic activation and inactivation of MLCK with increasing Pb 2+ concentration, but only in the presence of CaM, indicating that Pb 2+ interacts directly with CaM, not MLCK (97). Chao et al reported in a later study that Pb 2+ activated TnC, which subsequently stimulated myofibrillar ATPase (98). Therefore, the effects of Pb 2+ on different processes may occur indirectly via interactions with upstream proteins.…”
Section: Pb2+ Effects On Functional Activity Of Proteins Associated Wmentioning
confidence: 99%
“…The Pb 2+ ion can also occupy Ca 2+ -binding sites, and/or displace Ca 2+ in many proteins, including voltage-gated calcium channels (VGCCs) (140), troponin C (98), CaM (32), PKC (58), parvalbumin (64), and synaptotagmin (40). Moreover, CABPs have also been observed to bind a number of different non-essential metals in addition to Pb 2+ , including Sr 2+ , Hg 2+ , Cd 2+ and many lanthanides (141145).…”
Section: A New Perspective For the Molecular Basis Of Pb2+ Toxicitymentioning
confidence: 99%